Searching for RR Lyrae stars in the Canis Major overdensity - Mateu, C.; Vivas, K.; Zinn, R.; Miller, L. (Proceedings of the International Astronomical Union, 2006)
The Canis Major overdensity (CMa) was initially proposed to be the remnant of a tidally disrupting dSph galaxy. Since its nature is still subject of debate, the goal of the present work was to conduct a large-scale RR Lyrae survey in CMa, in order to see if there is an overdensity of these stars. The survey spans a total area of ∼ 34 sq. deg. with observations in V and R filters, made with the 1.0m Jürgen Stock Schmidt telescope at the National Astronomical Observatory of Venezuela. Current results in a subregion, including spectroscopic observations, show that the small number of RR Lyrae stars found can be accounted for by the halo and thick disk components of our Galaxy.